Attractive Toxic Sugar Bait (ATSB) For Control of Mosquitoes and Its Impact on Non-Target Organisms: A Review - Jodi M. Fiorenzano (International Journal of Environmental Research and Public Health, 2017)
Mosquito abatement programs contend with mosquito-borne diseases, insecticidal resistance, and environmental impacts to non-target organisms. However, chemical resources are limited to a few chemical classes with similar modes of action, which has led to insecticide resistance in mosquito populations. To develop a new tool for mosquito abatement programs that control mosquitoes while combating the issues of insecticidal resistance, and has low impacts of non-target organisms, novel methods of mosquito control, such as attractive toxic sugar baits (ATSBs), are being developed. Whereas insect baiting to dissuade a behavior, or induce mortality, is not a novel concept, as it was first introduced in writings from 77 AD, mosquito baiting through toxic sugar baits (TSBs) had been quickly developing over the last 60 years. This review addresses the current body of research of ATSB by providing an overview of active ingredients (toxins) include in TSBs, attractants combined in ATSB, lethal effects on mosquito adults and larvae, impact on non-target insects, and prospects for the use of ATSB.